2020
DOI: 10.1039/d0cc06212j
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-free cross-dehydrogenative arylation of unactivated benzylic C–H bonds

Abstract: The cross-dehydrogenative arylation of benzylic C–H bonds with arenes provides straightforward access to synthetically useful 1,1-diarylmethanes, from readily available starting materials. Current approaches suffer from limited substrate scope, requirement for...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…75.3 to give 75.4). 505 In a related example, the same monofluorination reaction was performed under flow conditions by circulating an acetonitrile solution of 76.1 through a transparent FEP tubing coiled around a glass cylinder (V = 28 mL, flow rate = 1 mL• min −1 ) containing a 105 W CFL. 287 Under these conditions, it was found that XA (5 mol %) could perform the monofunctionalization of the benzylic site to get 76.3 in 89% yield with a residence time of 28 min (temperature of the system = 40 °C).…”
Section: Formation Of C−s Bondsmentioning
confidence: 99%
See 2 more Smart Citations
“…75.3 to give 75.4). 505 In a related example, the same monofluorination reaction was performed under flow conditions by circulating an acetonitrile solution of 76.1 through a transparent FEP tubing coiled around a glass cylinder (V = 28 mL, flow rate = 1 mL• min −1 ) containing a 105 W CFL. 287 Under these conditions, it was found that XA (5 mol %) could perform the monofunctionalization of the benzylic site to get 76.3 in 89% yield with a residence time of 28 min (temperature of the system = 40 °C).…”
Section: Formation Of C−s Bondsmentioning
confidence: 99%
“…More recently, the above-mentioned procedure for the monofluorination of alkylaromatics was used to develop a one-pot, transition metal-free cross-dehydrogenative arylation of unactivated benzylic C–H bonds (Scheme ). In particular, FL was used to trigger the halogenation step, while the so-formed benzyl fluorides ( 75.2 ) were used as electrophilic partners in a nucleophilic substitution with electron-rich (hetero)­arenes (e.g. 75.3 to give 75.4 ) …”
Section: Formation Of C–y Bonds (Y ≠ C)mentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, trifluoromethyl-containing naphthaquinol 1a was selected as the acceptor of the benzyl equivalents (Table 1) as trifluoromethylcontaining quinols showed excellent reactivity toward the synthesis of trifluoromethylated arenes (Scheme 1b). [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Visiblelight promoted the construction of 1,1-diarylmethanes, which was initially investigated by the reaction of 1a with N,Ndimethyl aniline 2a in the presence of a photosensitizer, Ir( ppy) 3 (1 mol%), in acetonitrile (CH 3 CN, 2 mL) without any other additives under 15 W blue LED irradiation at room temperature (Table 1, entry 1); this reaction produced diarylalkane 3a in 42% isolated yield. The yield of 3a was improved to 47% when [Ir(dtbbpy)( ppy) 2 ][PF 6 ] was used as the photosensitizer (Table 1, entry 2).…”
Section: Resultsmentioning
confidence: 99%
“…15,31,[40][41][42][43] It was shown that 1,1-diarylmethane is a useful motif that is usually found in natural and bioactive compounds, such as bifemelane, benproperine, and tolterodine (Fig. 1), 44,45 which could be synthesized from acid-promoted Friedel-Crafts benzylation or transition-metal catalyzed cross-dehydrogenative benzylic arylation, etc. [46][47][48][49] These strategies generally require substrates with an α-activating group at the benzylic position or an additional base, oxidant, or radical initiator for activation.…”
Section: Introductionmentioning
confidence: 99%